Tyrosine kinase inhibitor interruptions, discontinuations and switching in patients with chronic-phase chronic myeloid leukemia in routine clinical practice: SIMPLICITY - Hehlmann, Rüdiger (American journal of hematology, 2019)
SIMPLICITY (NCT01244750) is an observational study exploring tyrosine kinase inhibitor (TKI) use and management patterns in patients with chronic phase-chronic myeloid leukemia in the US and Europe in routine clinical practice. Herein we describe interruptions, discontinuations and switching of TKI therapy during the initial 2 years of treatment among 1121 patients prospectively enrolled between October 1, 2010 and March 7, 2017. Patient characteristics were broadly similar between the imatinib (n = 370), dasatinib (n = 376), and nilotinib (n = 375) cohorts. Treatment interruptions occurred in 16.4% (year 1) and 4.0% (year 2) of patients, mainly attributed to hematologic intolerances. Treatment discontinuations occurred in 21.8% (year 1) and 10.2% (year 2) of patients, with the highest rate within the first 3 months for intolerance. Switching of TKI was seen in 17.8% (year 1) and 9.5% (year 2) of patients. Significant associations were found between TKI switching and female gender (year 1), age ≥65 years at diagnosis (year 2) and treatment with imatinib (year 2). Intolerance was the most common reason given for patients discontinuing and for switching TKI therapy; however resistance was also cited. Lack of response monitoring in routine clinical practice may have resulted in lower identification of resistance in this dataset. Data from SIMPLICITY suggest that, in routine clinical practice, intolerance and resistance to TKIs influence decisions to change treatment. Changes in TKI therapy are frequent, with nearly a third of patients discontinuing their first-line TKI.
First published: 05 October 2018
Gesehen am 11.07.2019